Understanding Voluntary NSSI Disclosure - Mirichlis, Sylvanna Christina (Curtin University, 2024)
Non-suicidal self-injury (NSSI) is the deliberate damage a person causes to their body tissue without the intent to die. Although disclosing one’s NSSI can potentially catalyse support, relief, and self-acceptance, many do not disclose their experience. The aim of this PhD was to better understand voluntary disclosure of NSSI. Across five studies, factors and processes that inform NSSI disclosure were investigated. The findings are surmised in the proposal of a novel framework of NSSI disclosure.